Physical, functional and audiological assessment of the elderly to proceed with the hearing-aid fitting - Bernal Zafra, Sebastián (Auditio, 2021)
In the elderly, there are two situations: one, their need to listen to the social isolation caused by deafness and the other, the disappointment they cause, the negative results obtained in the prosthetic adaptation that do not reach the objectives set by them, which forces you not to use the prosthesis. This work intends, firstly, that the coincidence of these two situations does not occur, and secondly, to make hearing care professionals aware that prosthetic adaptation is much more than a simple commercial transaction, that the hearing care professional is treating a patient more than to a client and that their professional work should be focused on prosthetically solving an auditory pathology based on objective and scientific criteria. For this, we have protocolized the data collection to facilitate the hearing care professional, its study and decision making. This is what allows us to know the elderly, not only in terms of their auditory pathology, but also in terms of their coexistence needs and desirable degree of well-being, which in turn allows us to act correctly in the choice of prosthesis and of the ear to appear. The results will always be pleasant, whether or not an adaptation is made, since we are in a position to explain the causes and their why, which satisfies the elderly who does not feel cheated, as if the adaptation is carried out since they see compliments your goals in a rewarding way.